Sustainability priorities across the strategic and operational level in packaging development. Issue 12 (12th September 2019) - de Koeijer, Bjorn; Gelhard, Carsten; ten Klooster, Roland
Abstract : Sustainability is well‐established in many companies' strategic postures. However, executing sustainability‐related goals often lags at the operational level. This study analyses how decision‐making processes in packaging development at different hierarchical levels are characterized in achieving a sustainability consensus. This research focuses on the alignment of the strategic and operational levels of packaging development in relation to the integration of sustainability considerations. This materializes in a stakeholder perspective on packaging development and an analysis of targets aiming for the integration of sustainability considerations in such development processes. The involvement and decision making by internal stakeholders, the involvement of external stakeholders and sustainability target setting are considered as conditions causing the outcome of interest: levels of sustainability implementation on both the strategic and the operational levels of packaging development. By using a set‐theoretic method, we address that different compositions of stakeholder involvement and target setting might cause the same level of sustainability priority at the strategic and operational levels. For data analysis, we use a fuzzy‐set qualitative comparative analysis (fsQCA) with empirical data derived from survey responses by packaging experts. This approach is motivated by its ability to address the complexity of the interplay of case characteristics within development processes. The research findings provide several indications of a limited alignment of a company's strategic sustainability ambition with the operational activities of multidisciplinary packaging development teams. The insights on the sustainability‐related configurations of stakeholders and target setting provide guidance for managing projects across the strategic and operational levels in improving sustainable packaging development. Abstract : This research focuses on the alignment of the strategic and operational levels of packaging development in relation to sustainability considerations, from a stakeholder perspective. By using a set‐theoretic method (fuzzy‐set qualitative comparative analysis [fs QCA]), we address that different compositions of stakeholder involvement and target setting might cause the same level of sustainability priority at the strategic and operational levels. The research findings provide indications of a limited alignment of strategic sustainability ambitions with the operational activities of packaging development teams.